Unsteady mixed convection boundary layer flow from elliptic cylinder - Chung, Kuet Siong (2010)
The unsteady mixed convection boundary layer flow of a Newtonian fluid near the region of the stagnation point over an elliptic cross section of a cylinder in both horizontal (blunt elliptic cylinder) and vertical (slender elliptic cylinder) is considered in this project. The governing system of higher order partial differential equations is reduced into a system of first order differential equations. Then, the transformed equations are solved numerically by Keller-box scheme. The numerical results are obtained for various values of the Prandtl numbers and parameter (parameter for major and minor axes of the cylinder). Meanwhile, the features of assisting and opposing flow are investigated.